Metabolomic and Cytotoxicity Profiles of Ethanol Extract of Peronema canescens Jack on Human Non-small Lung Cancer Cell A549 - Nuri Anjayani; Senya Putri Amalia; Linda Sukmarini; Hady Anshory Tamhid; Gian Primahana; Asih Triastuti (Fakultas Farmasi Universitas Andalas, 2025)
Cancer has a high prevalence and mortality in the world. Cancer treatment is still hampered by high levels of side effects, drug resistance and the lack of affordable prices for anticancer drugs. It is necessary to develop new anticancer drugs to help overcome this problem. One of the plants that has the potential to be developed as an anticancer drug is Sungkai (Peronema canescens Jack). This study aims to determine the cytotoxic activity of sungkai leaf and identify its metabolomic profile. The sungkai leaves were macerated for 24 hours with 96% ethanol. Metabolomic profiles were analyzed with Ultra High-Performance Liquid Chromatography-High Resolution Mass Spectrometry (UHPLC-HRMS). Chemical structure identification was performed by MS-DIAL and MS-FINDER platforms. The ethanol extract of sungkai leaves was analyzed for its cytotoxic activity using the MTT test on A549 lung cancer cells and its selectivity on normal HDFa fibroblast cells. The ethanol extract of sungkai showed IC50 105,21 µg/mL on A549 cells and no cytotoxic activity against normal HDFa cells. Based on the metabolomic analysis, 7 furano terpenoid compounds were detected in the ethanol extract, namely peronemin A2; A3; B1; B2; B3: C1; and D1 along with other compounds. In conclusion, the ethanol extract of P. canescens leaves has cytotoxic and selective activity against A549 lung cancer cells, and potential to be further developed as an anticancer drug candidate. Peronemins and other substances like flavonoids and polyphenols may be linked to the cytotoxic properties of sungkai leaves